Evaluation of the Organoleptic Quality of Fresh Sea Fish Based on SNI 2729:2013 at Legi Songgolangit Market, Ponorogo Regency - Andika David Saputra; Fadhilla Ardyaneta Anggraini; Alya Himmati (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
This study aims to evaluate the freshness level of sea fish sold at Legi Songgolangit Market, Ponorogo Regency. The method used in this study is a survey and interview with a purposive sampling technique. Fish quality assessment refers to SNI 2729: 2013 for five types of fresh fish, namely tuna (Thunnus sp.), mackerel (Scomberomorus commerson), salmon (Oncorhyncus masou), mackerel (Restrelliger sp.), and squid (Loligo sp.), with three samples of each. The parameters observed include the condition of the eyes, gills, meat texture, aroma, and body mucus with a score of 1-9. The results of the study showed that tuna, mamckerel, and salmon experienced a decline in quality with an average organoleptic value of 4-5, while mackerel and squid had a better freshness level with an average value of 8. This shows that the freshness level of fish at Legi Songgolangit Market varies between types of fish, so better post-harvest handling is needed to maintain the quality of fish in traditional markets.